FXR-regulated COX6A2 triggers mitochondrial apoptosis of pancreatic β-cell in type 2 diabetes - Lianqi Shao; Xiangchen Kong; Simian Lv; Xingsheng Shu; Xiaosong Ma; Xiaojiao Ai; Dan Yan; Ying Ying (Cell Death and Disease)
Abstract Pancreatic β-cell apoptosis plays a crucial role in the development of type 2 diabetes. Cytochrome c oxidase subunit 6A2 (COX6A2) and Farnesoid X Receptor (FXR) have been identified in pancreatic β-cells, however, whether they are involved in β-cell apoptosis is unclear. Here, we sought to investigate the role of FXR-regulated COX6A2 in diabetic β-cell apoptosis. We found that COX6A2 expression was increased in islets from diabetic animals, whereas FXR expression was suppressed. Notably, overexpression of COX6A2 facilitated β-cell apoptosis, whereas its deficiency attenuated this process and ameliorates type 2 diabetes, suggesting a pro-apoptotic role of COX6A2 in β-cells. Mechanistically, increased COX6A2 interacted with and enhanced the expression of voltage-dependent anion channel 1 (VDAC1), thereby promoting the mitochondrial translocation of Bax, leading to the release of cytochrome c from the mitochondria to the cytoplasm and ultimately causing β-cell apoptosis. Moreover, FXR negatively regulated COX6A2 expression through the inhibition of histone acetyltransferase p300 occupancy, diminishing histone H3 acetylation at lysine 27 on the Cox6a2 promoter. Furthermore, the deficiency of FXR intensified β-cell apoptosis under diabetic situations. Thus, it is probable that in diabetogenic environments, reduced FXR expression contributes to enhanced COX6A2 expression, culminating in β-cell apoptosis. These findings emphasize the essential involvement of the FXR/p300 pathway-controlled COX6A2 in β-cell apoptosis, revealing a previously undiscovered mechanism underlying diabetic β-cell apoptosis.